Exploring the aftermath of hematopoietic cell transplantation: 18-year insights into post-transplant neoplasms - Rihani, Rawad; Amer, Shrouq; Halahleh, Khalid; Hashem, Hasan; Abdel Rahman, Zaid; Baqain, Laith; Abu Shanap, Mayada; Sultan, Iyad; Qudeimat, Amr (Frontiers in Oncology, 2025)
IntroductionSurvival post-hematopoietic stem cell transplantation (HCT) is improving, with an increasing number of survivors. Subsequent neoplasms (SNs) following HCTs are of particular concern.MethodsBetween January 2003 and December 2022, HCT recipients’ records were retrospectively reviewed.ResultsAt a median follow-up of 108 months (range, 0.13-215), 2659 patients received HCTs. Of those, 1131 (43%) were <18 years old. Allogeneic HCTs were conducted in 1476 (56%) patients. Myeloablative conditioning (MAC) was utilized in 2157 (81%), and 583(22%) received TBI. At a median of 9 years following transplant, forty-three patients developed SNs (1.6%) with a median age at time of HCT of 27.6 years (range, 2.8-64.8). Of those: 32 were males (74%), 20 received full HLA-matched allogeneic HCTs (46.5%), two (4.6%) had unrelated cord blood HCT (UCB), and one (2.3%) received haplo-HCT, whereas autologous HCTs accounted for 46.6% (n=20). Underlying diseases were: ALL(13.9%), AML(11.6%), Hodgkin Lymphoma(13.9%), Non-Hodgkin lymphoma(13.9%), Multiple Myeloma(18.6%), Fanconi Anemia(6.9%), CML(6.9%),Neuroblastoma(2.3%), and thalassemia (2.3%).); cGVHD occurred in (74%), and CMV infection/reactivation in (60.5%). Stem cell source included peripheral blood in (81.4%), BM in (3.9%), and UCB in (4.7%). Conditioning regimens were MAC (81.4%) vs RIC (18.6%). TBI-based regimen was utilized in 14 patients (32.5%). Subsequent hematologic malignancies accounted for 32.5% of SNs. While subsequent solid neoplasms occurred in 65.2%, and PTLD occurred in 2.3%. The probability of 5-year overall survival after a SN was 58.2%.ConclusionsSNs adversely impact the overall survival and quality of life of HCT survivors. In our cohort, the rate of post-HCT SNs was lower than that in the literature; however, longer follow-up of our cohort is needed.